Torres entre tramas y texturas : cuerpo y ciudad en la obra artistica del maestro Adolfo Leon Torres Rodriguez. - Cecilia, María (UNIVERSIDAD DEL CAUCA, 2018)
The present book, written by the university professor María Cecilia Alvarez, deals with the interpretation and analysis of the artistic work of the Paganan teacher in plastic arts Adolfo León Torres Rodríguez. Body, city and work, constitute the three thematic axes that guided the work hypothesis: -how the city - in this case, Popayán (Colombia) - and the body, understood as the life of the artist are creatively configured on the canvas, giving meaning and intentionality to the aesthetics of his work.